A practical guide to prairie reconstruction - Kurtz, Carl (Bur oak book., 2013)
Thirty-five years and many acres after planting his first patch of prairie flowers, Carl Kurtz is considered one of the deans of the great tallgrass prairie revival. The Prairie Enthusiast called the 2001 edition of his book a "readable and understandable introduction to prairie and the general steps in carrying out a reconstruction." Now this second edition reflects his increased experience with reconstructing and restoring prairie grasslands. Kurtz has completely revised every chapter of the first edition, from site selection and harvest to soil preparation, seeding.